2005
DOI: 10.1086/428391
|View full text |Cite
|
Sign up to set email alerts
|

The Proto–Planetary Nebula M1‐92 and the Symbiotic Star MWC 560: Two Evolutionary Phases of the Same Type of Object?

Abstract: Important similarities between the objects M1-92, a proto-planetary nebula of bipolar morphology, and MWC 560, a symbiotic star with a jet, have been found. A brief review of the previous studies for both objects is presented for the purpose of proposing mechanisms that best explain these similarities, since up to now both objects have been studied independently. From the comparison of the spectra of both objects, the existence of a jet is confirmed for the proto-planetary nebula M1-92, as well as its binary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Bujarrabal et al (1998b) estimated that the mass of the ionized gas in the nebula is only about 10 −3 M , and Arrieta et al (2005) concluded that the present ionized mass loss is very low, 3 × 10 −13 M yr −1 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Bujarrabal et al (1998b) estimated that the mass of the ionized gas in the nebula is only about 10 −3 M , and Arrieta et al (2005) concluded that the present ionized mass loss is very low, 3 × 10 −13 M yr −1 .…”
Section: Introductionmentioning
confidence: 93%
“…The central star has a spectrum compatible with T eff = 6500 K and log g = 0.5, although at short wavelengths it shows an excess that can be fitted with the presence of a secondary star of T eff = 18 000 K and log g = 5.0 (Arrieta et al 2005). The distance to M 1-92 has been estimated as 2.5 kpc, adopting a nominal luminosity of 10 4 L for a post-AGB star (Cohen & Kuhi 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to include jets in either the hydrodynamic calculations because of the supersonic velocities, or the radiative transfer calculations. Nevertheless, the possibility of a jet contribution to either Hα and Hβ formation has been demonstrated by several studies (Budaj & Richards 2004;Arrieta et al 2005). …”
Section: Jet Launching In the Accretion Disk Of The Companionmentioning
confidence: 99%
“…Many new observations and theoretical studies since the turn of the Millennium further consolidated the jet-shaping scenario of many PNe (e.g., Parthasarathy et al 2000;Bujarrabal et al 2001;Miranda et al 2001;Corradi et al 2001b;Guerrero et al 2001;Imai et al 2002;Riera et al 2003;Vinković et al 2004;Huggins et al 2004;Peña et al 2004;Balick & Hajian 2004;Arrieta et al 2005;Oppenheimer et al 2005;Sahai et al 2005;Vlemmings et al 2006;Miranda et al 2010;Nakashima et al 2010;Phillips et al 2010;Sahai et al 2011;Szyszka et al 2011;López et al 2012;Clark et al 2013;Pérez-Sánchez et al 2013;Vlemmings et al 2014;Fang et al 2015 Dennis et al 2008Dennis et al , 2009Lee et al 2009;Huarte-Espinosa et al 2012;Velázquez et al 2012;Balick et al 2013;Velázquez et al 2014 for theoretical studies; these papers composed a small fraction of the papers studying jets in PNe). X-ray observations seem also to support the presence of jet-inflated bubbles and of jets Sahai et al 2003), similar to X-ray jets in symbiotic systems (e.g., Kellogg et al 2001;Galloway & Sokoloski 2004).…”
Section: Pn Morphologiesmentioning
confidence: 99%